A hybrid Simulation model for Green Logistics Assessment in Automotive Industry - Abduaziz, Oumer; Jack, Kie Cheng; Razman, Mat Tahar; Ramaraju, Ramgopal Varma (Elsevier Ltd, 2015)
The aim of this paper is to assess green logistics practices in automotive industry by using simulation method. In automotive industry logistics involves the integration of manufacturing, assembly, and distribution activities. The proposed model will assist decision makers acquire an in-depth understanding of environmental impacts and costs associated. The main issues that should be considered include: Carbon Dioxide (CO)emission, re-use and recycling of material, waste disposal and energy utilization. A combined model of system dynamics (SD) and discrete event simulation (DES) will be used. The trade-offs between costs and environmental protection will be analyzed. The results indicate that there exist positive tradeoffs between green practices (CO2reduction, promoting recycling, and water and energy conservation) and operational costs.